Implementasi Tridarma Perguruan Tinggi Tentang Pelayanan Kesehatan “Sunatan Massal”AGDOSI Bekerjasama Alumi SPK Depkes Ujung Pandang - Djunaedi, Djunaedi; Jabir, M. Agus; Asrianto, Asrianto; Rante, Anshar; Kamaruddin, Muh. Ihsan; Mustamin, Rini (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Circumcision is cutting part of the foreskin of the penis to the entire glans so that the corona radiate is clearly visible. The penis is one of the tubular organs that passes through the urethra and is used to channel urine and to channel semen and sperm together into the vaginal canal during intimate or sexual intercourse. One effort so that every child can perform Sunnat is by carrying out Sunnat activities in the community. From this mass circumcision activity, it is hoped that many children in Indonesia, especially the city of Makassar, will be able to be circumcised, thereby achieving the goal of increasing the health status and good growth of Indonesian children. The method used is a mass Sunnatan in collaboration with the Association of Teachers and All Indonesia (AGDOSI) with Alumni of SPK Depkes Ujung Pandang 98 in community service activities to meet the demands of maximum health services, in accordance with what is expected by the community in the health sector through Human Resources the professional one. The community is very supportive and supportive of the activities carried out by the PkM team. This PkM activity was successful and ran smoothly according to the hopes and objectives of the PkM team.